SWOT analysis of the international freight road transport sector of Ukraine - Totska, Olesia Leontiivna; Prosvirnikov, Maksym Valeriiovych (Харківський національний університет імені В. Н. Каразіна, 2025)
In ensuring the free movement of goods between Ukraine and its external partners, in particular the EU, the sphere of international freight road transportations of Ukraine plays an important role. Problem statement. SWOT analysis can be used to study its external and internal environment. Unresolved aspects. A SWOT analysis matrix of the sphere of international freight road transportations of Ukraine has been constructed. Purpose of the article. The purpose of the article is to identify the strengths and weaknesses, as well as opportunities and threats of the sphere of international freight road transportations of Ukraine. Main material. A number of important advantages have been identified: convenient geographical location of the state; extensive network of highways; experienced carriers; competitive cost of services; access to European markets. A number of weaknesses have been identified: unsatisfactory condition of a significant part of the infrastructure; shortage of qualified drivers; difficulties with processing documents and obtaining permits for international transportations; technical condition of the fleet; low level of digitalization; corruption. The following opportunities have been identified: expanding cooperation with the EU; investments in modernization; growing demand for transportations; integration with new markets in Central Asia, the Caucasus, and the Middle East; introduction of innovations. Certain threats have been identified: military operations on the territory of the state; increased competition from carriers from neighboring countries; lack of sufficient funding to comply with EU environmental standards; economic instability; restrictions on border crossing. Conclusions. For the further development of the international freight road transportations sector in Ukraine, it is advisable to apply the “Mini-Maxi” strategy, which is aimed at minimizing internal weaknesses based on the use of external opportunities.
У забезпеченні вільного руху товарів між Україною та її зовнішніми партнерами, зокрема ЄС, важливу роль відіграє сфера міжнародних вантажних автомобільних перевезень України. Постановка проблеми. Для дослідження її зовнішнього та внутрішнього середовища можна застосувати SWOT-аналіз. Нерозв’язані аспекти. Побудовано матрицю SWOT-аналізу сфери міжнародних вантажних автомобільних перевезень України. Мета статті. Метою статті є ідентифікація сильних і слабких сторін, а також можливостей і загроз сфери міжнародних вантажних автомобільних перевезень України. Основний матеріал. Визначено низку важливих переваг: зручне географічне розташування держави; розгалужена мережа автомобільних доріг; досвідчені перевізники; конкурентна вартість послуг; доступ до європейських ринків. Виділено низку слабких сторін: незадовільний стан значної частини інфраструктури; дефіцит кваліфікованих водіїв; складнощі з оформленням документів та отриманням дозволів на міжнародні перевезення; технічний стан автопарку; низький рівень цифровізації; корупція. Ідентифіковано такі можливості: розширення співпраці з ЄС; інвестиції в модернізацію; зростання попиту на перевезення; інтеграція з новими ринками Центральної Азії, Кавказу, Близького Сходу; впровадження інновацій. Виділено певні загрози: воєнні дії на території держави; посилення конкуренції зі сторони перевізників із сусідніх країн; відсутність достатнього фінансування на дотримання екологічних стандартів ЄС; економічна нестабільність; обмеження на перетин кордону. Висновки. Для подальшого розвитку сфери міжнародних вантажних автомобільних перевезень України доцільно застосувати стратегію «Міні-Максі», яка спрямована на мінімізацію внутрішніх слабких сторін на основі використання зовнішніх можливостей.
Keywords: international road freight transportation; Ukraine; EU; SWOT analysis; strengths; weaknesses; opportunities; threats; strategy; міжнародні вантажні автомобільні перевезення; Україна; ЄС; SWOT-аналіз; сильні сторони; слабкі сторони; можливості; загрози; стратегія; N70; 338.47(477):005.525